2007
DOI: 10.2989/ajms.2007.29.2.4.187
|View full text |Cite
|
Sign up to set email alerts
|

Non-random habitat use by coral reef fish recruits in Mafia Island Marine Park, Tanzania

Abstract: The habitat use by nearly 3 000 reef fish recruits, comprising 56 taxa, at seven sites in Mafia Island Marine Park, Tanzania, were examined. The study was carried out following the 1998 global coral bleaching event and all sites but one were dominated by dead coral and rubble. Mean recruit densities ranged between 0.1 m -2 and 0.7 m -2 among sites. Although live coral represented only 15% of the overall substrate composition, almost half of all observed recruits were found associated with this substrate. Poole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 36 publications
0
7
1
Order By: Relevance
“…Yet, Aubanel et al (1999) have shown that the fringing reefs were dominated by living corals before embankment around Moorea. Other studies confirmed that the building of embankments was often associated with the death of corals and the overgrowth of macro-algae through water pollution (e.g., Feary et al 2007;Garpe and Ohman 2007). However, our results did not support a reduction in the number of fish individuals on fringing reefs.…”
Section: Resultscontrasting
confidence: 73%
“…Yet, Aubanel et al (1999) have shown that the fringing reefs were dominated by living corals before embankment around Moorea. Other studies confirmed that the building of embankments was often associated with the death of corals and the overgrowth of macro-algae through water pollution (e.g., Feary et al 2007;Garpe and Ohman 2007). However, our results did not support a reduction in the number of fish individuals on fringing reefs.…”
Section: Resultscontrasting
confidence: 73%
“…Jones et al (2004) suggested that declines in diversity following coral loss were partially attributable to reliance on living coral at earlier life history stages. This suggestion is supported by findings that coral association among juveniles is much higher than that among adult conspecifics of some reef fish (Feary et al 2007;Garpe and Ö hman 2007;Wilson et al 2008). Up to 65% of fishes may be reliant on corals at settlement (Jones et al 2004) suggesting that if coral recovery from disturbance is negligible, lagged declines in diversity of fishes may occur due to natural mortality combined with minimal population replenishment.…”
Section: Discussionmentioning
confidence: 79%
“…Many reef fish species use live coral as settlement habitat , Garpe & Öhman 2007, and although it is clear that settlers can distinguish between live and dead coral (Öhman et al 1998(Öhman et al , Feary et al 2007b, it is currently unknown if they avoid settling onto bleached corals. Reef fish use visual and chemical cues to recognise their settlement habitat (Booth 1992, Elliott et al 1995 and the loss of pigmentation and physiological stress corals experience during bleaching could potentially disrupt these cues.…”
Section: Introductionmentioning
confidence: 99%